AI dan Konsep Dharma: Etika Kecerdasan Buatan dalam Bingkai Filsafat Hindu - Griya Danika, I Wayan Sindia; Wiranata, Anak Agung Gede (Widya Katambung, 2025)
This study aims to examine the relevance of the Hindu philosophical principle of Dharma as an alternative ethical framework in the development and application of artificial intelligence (AI). The research addresses the growing ethical crisis in modern AI systems, particularly concerning algorithmic bias, system autonomy, and the absence of moral accountability. Employing a qualitative philosophical-hermeneutic approach, this study analyzes classical Hindu texts such as the Bhagavad Gita, Upanishads, and Manusmṛti, alongside contemporary academic literature. Data collection techniques include textual analysis and semi-structured interviews with Hindu clerics, philosophy scholars, and AI ethics experts in Bali and Yogyakarta. The analysis reveals that Dharma offers a holistic ethical framework—encompassing moral, spiritual, and cosmological dimensions—that bridges the gap between technological efficiency and moral responsibility. Three central themes emerged from the findings: (1) moral responsibility based on svadharma (individual duty), (2) ahimsa (non-violence) ethics in algorithmic design, and (3) the spiritualization of technology as a means to preserve cosmic harmony. These insights contribute theoretically to the development of a more pluralistic, culturally rooted AI ethics discourse and offer practical implications for designing context-aware and human-centered AI policy frameworks. The study concludes that integrating Eastern philosophical values into technology ethics curricula and global AI governance is essential. Future research is encouraged to explore ethical principles from other religious traditions and examine the application of Dharma-based ethics in participatory, community-driven technology design.